1,4-Disubstituted 1H-1,2,3-Triazole Containing Peptidotriazolamers: A New Class of Peptidomimetics With Interesting Foldamer Properties - Schröder, David C.; Kracker, Oliver; Fröhr, Tanja; Góra, Jerzy; Jewginski, Michał; Nieß, Anke; Antes, Iris; Latajka, Rafał; Marion, Antoine; Sewald, Norbert (Frontiers in Chemistry, 2019)
Peptidotriazolamers are hybrid foldamers with features of peptides and triazolamers, containing alternation of amide bonds and 1,4-disubstituted 1H-1,2,3-triazoles with conservation of the amino acid side chains. We report on the synthesis of a new class of peptidomimetics, containing 1,4-disubstituted 1H-1,2,3-triazoles in alternation with amide bonds and the elucidation of their conformational properties in solution. Based on enantiomerically pure propargylamines bearing the stereogenic center in the propargylic position and α-azido esters, building blocks were obtained by copper-catalyzed azide-alkyne cycloaddition. With these building blocks the peptidotriazolamers were readily available by solution phase synthesis. A panel of homo- and heterochiral tetramers, hexamers, and heptamers was synthesized and the heptamer Boc-Ala-Val-Ψ[4Tz]Phe-LeuΨ[4Tz]Phe-LeuΨ[4Tz]Val-OAll as well as an heterochiral and a Gly-containing equivalent were structurally characterized by NMR-based molecular dynamics simulations using a specifically tailored force field to determine their conformational and solvation properties. All three variants adopt a compact folded conformation in DMSO as well as in water. In addition to the heptamers we predicted the conformational behavior of similar longer oligomers i.e., Boc-Ala-(AlaΨ[4Tz]Ala)6-OAll as well as Boc-Ala-(d-AlaΨ[4Tz]Ala)6-OAll and Boc-Ala-(GlyΨ[4Tz]Ala)6-OAll. Our calculations predict a clear secondary structure of the first two molecules in DMSO that collapses in water due to the hydrophobic character of the side chains. The homochiral compound folds into a regular helical structure and the heterochiral one shows a twisted “S”-shape, while the Gly variant exhibits no clear secondary structure.